Pengaruh Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Pada Kantor Samsat Badung Dengan Insentif Pajak Sebagai Variabel Moderasi - Ayu, Ni Luh Ayu Sri Kusuma Dewi; I Nyoman Putra Yasa; Nyoman Ari Surya Dharmawan (Universitas Pendidikan Ganesha, 2025)
The purpose of this study was to determine the effect of taxpayer awareness on compliance of motor vehicle taxpayers at the Badung SAMSAT office with tax incentives as a moderating variable. The population in this study were all motor vehicle taxpayers registered at the Badung SAMSAT office totaling 457,080 people, using purposive sampling. The number of samples that were successfully processed in this study were 100 respondents. This study uses partial least square (PLS) data analysis techniques using SmartPLS 4.0 software. The results obtained in this study are taxpayer awareness has a positive and significant effect on motor vehicle taxpayer compliance, tax incentives have a positive and significant effect on motor vehicle taxpayer compliance, and tax incentives weaken or cannot moderate the effect of motor vehicle taxpayer awareness at the Badung SAMSAT office.